Virtual environments and meaningful learning in university students of the Faculty of Education of the UNMSM - Villanueva Salas, Elsa A. (2023)
Recent changes in higher education are challenging and transcendental; in this context; the delivery of classes in virtual environments requires exhaustive preparation, dedication and constant feedback so that significant learning can be produced among university students at the Faculty of Education of the UNMSM. The objective of this article is to determine how virtual environments and meaningful student learning are related. The approach is a quantitative, non-experimental design, correlational level and basic type. The sample was formed by 105 students and as a data collection instrument the survey was used through a questionnaire of 20 items for each of the investigation variables. The validity was carried out by the judgment of experts, with a reliability of Cronbach's Alpha greater than 0.94 and 0.96, resulting in both variables having an acceptable reliability and proceeding to its application, in this way the Pearson correlation was 0.853, demonstrating that There is a strong positive relationship between virtual environments and significant learning, this implies that the use of tools and virtual platforms improves the quality and effectiveness of the learning process, fostering a deeper and longer-lasting understanding of its contents. In conclusion, EVs used correctly are a useful and effective tool for improving learning compared to other traditional methods.